Analysis of tax assessment by assembly and property development activities in fragmented urban lands – Gwangjin District, Seoul, South Korea - Shin, Seungwoo; Lee, Yeonjae; Taltavull de La Paz, Paloma (International Journal of Strategic Property Management, 2023)
Due to the land readjustment project in Gwangjin District, Seoul, Korea, in the 1970s, Gwangjin was characterized as a single-family residential area for individual households. Over the following 40 years, the land-use situation changed dramatically, and ironically, there is now a too-fragmented residential area and very insufficient commercial areas. We employed a balanced panel data analysis. The data for this study were 24,177 parcel tax assessments and land assembly, split, zoning change, and property development activities over nine years from 2011 to 2019. We found that de facto land assembly would affect the tax assessment by delaying it a year more than it is when the development is approved, while formal land assembly did not. Development activity itself increased the assessment for that year only. Finally, formal land assembly in the commercial zone increased the assessment only for the following year, while property development in the residential zone increased the assessment for that year only. We recommend that the government provide land-assemblyfriendly policy incentives to allow for much larger property developments in both residential and commercial zones. The research on land and property development activities’ impact on tax assessment can provide a reasonable basis for the government’s tax assessment institution building.